Beyond Framing: Influences of subject-photographer interactions on visual journalism - Thomson, T. J.; Greenwood, Keith (Journalism practice, 2017)
Visual news media's framing has been well studied; however, production factors and cultural conditions involved in photographer-subject interactions have attracted less scholarly attention although they are no less influential in determining the depiction. Guided by social constructionism theory, in-depth interviews with staff photojournalists at a daily community newspaper in the Midwest and an analysis of their work revealed 22 variables that impact how and why images look the way they do. Photojournalists have complete control of only two of these variables, share partial control of 13, but have no control over the remaining seven. The photographers also shared insights into how to improve their journalism's verisimilitude when dealing with reactive subjects. The results support concepts of social constructionism that the subjects of photographs are most comfortable with photographers who share similar characteristics, but that some characteristics can have greater influence. The results also highlight areas where photographers might focus in pursuit of authenticity in journalistic photographs.